Evidence for Overlapping Visual Processing Difficulties in Adult ADHD and Visual Stress. - BarNir, Aviva; Shaked, Haya; Elad, Shulamit; Tosta, Sandra (Perceptual & Motor Skills, 2023)
We investigated the viability of spectral filters as an adjunctive treatment for adults with both ADHD and visual processing difficulties. Fifty-nine adults (age 18-50), diagnosed with both ADHD and visual stress received either spectral filters (n = 39) or no intervention (n = 20) to address visual processing difficulties. We administered the MOXO d-CPT, a computer based continuous performance test, before the intervention and one hour after the intervention to assess any short-term change in the participants' attention profile. We used the American Psychiatric Association's Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5) before and 3–6 months after the intervention to assess any long-term intervention impact after 3–6 months. The intervention group had significant short- and long-term improvements in overall attention compared to the control group (X(1, N = 59) = 20.10, p <.001). On the DSM-5, 49% of participants with short term and 64% with long-term intervention no longer met criteria for an ADHD diagnosis. Findings suggest that spectral filters may be an adjunctive treatment for many adults suffering from perceptually-based attention issues common to visual stress and ADHD.